(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article is devoted to the essence of the evaluation category from an axiological point of view, within the framework of the theory of value, the definition of an object in terms of satisfaction or dissatisfaction with established requirements, needs, desires descriptive, the emergence of evaluation depends on the needs and motives of a person, the evaluation is devoted to an important cognitive mechanism that requires the participation of pragmatic factors.